Robust bone regeneration through endochondral ossification of human mesenchymal stem cells within their own extracellular matrix. (October 2019) - Liu, Yuwei; Kuang, Biao; Rothrauff, Benjamin B.; Tuan, Rocky S.; Lin, Hang
Abstract: Mesenchymal stem cells (MSCs) embedded in their secreted extracellular matrix (mECM) constitute an exogenous scaffold-free construct capable of generating different types of tissues. Whether MSC-mECM constructs can recapitulate endochondral ossification (ECO), a developmental process during in vivo skeletogenesis, remains unknown. In this study, MSC-mECM constructs are shown to result in robust bone formation both in vitro and in vivo through the process of endochondral ossification when sequentially exposed to chondrogenic and osteogenic cues. Of interest, a novel trypsin pre-treatment was introduced to change cell morphology, which allowed MSC-mECM constructs to undergo the N-cadherin-mediated developmental condensation process and subsequent chondrogenesis. Furthermore, bone formation by MSC-mECM constructs were significantly enhanced by the ECO protocol, as compared to conventional in vitro culture in osteogenic medium alone. This was designed to promote direct bone formation as seen in intramembranous ossification (IMO). The developmentally informed method reported in this study represents a robust and efficacious approach for stem-cell based bone generation, which is superior to the conventional osteogenic induction procedure.